Development of an information APP for seismological risk situations for the city of Bogotá (2019)
(Eng) The objective of the article is to implement the PDVS methodology to develop an application (apps) for mobile devices related to seismic risk situations that allows citizens to hav e timely information about seismic risks. The objectives of the research lead to choosing a methodology of applied research type, allowing to develop a technological tool called BOGSAT (Early Warning System). The results allow us to identify that this type of applications constitute dissemination mechanisms for the prevention of risks and disasters. Likewise, the study determined that in Bogotá it is necessary to consolidate databases to provide information to the inhabitants of the city. In conclusion, thi s application favors the consolidation between technology and collaborative environments, in such a way that they are references for obtaining information in disaster prevention.